Potential benefits of anticoagulant doses of low molecular weight heparin in COVID-19: An observational retrospective study (Emergency Care Journal, 2021)
Hypercoagulability is a common complication of the systemic inflammation related to coronavirus disease 2019 creating debate within the critical care community on the therapeutic utility of Low Molecular Weight Heparin (LMWH). We collected data on consecutive patients with COVID-19 admitted to the Emergency Department of Castel San Giovanni Hospital, between February 29th and April 7th, 2020. Exclusion criteria were age
Keywords: Pneumonia; COVID-19; thrombosis; heparin; mortality